A CROSS-SECTIONAL STUDY TO ASSESS THE KNOWLEDGE OF SKILLED BIRTH ATTENDANTS IN INDORE DISTRICT OF MADHYA PRADESH - Rathore, Deepika; Pandey, Dhruvendra; Gupta, Mahesh; Sinha, Umesh (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to assess the knowledge of skilled birth attendants (SBAs) in providing antenatal care, intranatal care, management of complications, and postnatal care. Methods: A cross-sectional study was done at primary and secondary level of health-care delivery centers of Indore district in Madhya Pradesh. Health centers were selected by simple random sampling. SBA-trained health personnel were selected from the study health centers and their knowledge was assessed through pre-designed, semistructured questionnaire prepared from “Trainers manual for training of SBA” of MOHFW. Result: A total of 80 trained SBAs were selected from the study health centers. Knowledge regarding postnatal care was highest (88.5%) followed by knowledge regarding antenatal care (86.8) and intranatal care (82.3%). Knowledge regarding the management of complications was lowest (75.8%). Overall, average % of knowledge regarding various subtopics among Medical Officer/AYUSH Medical Officer was 88.5%, followed by staff nurse (SN) was 85.5, lady health visitor (LHV) was 83.4%, and auxiliary nurse midwife (ANM) was 76.1%. Average % in the management of complications was lowest among LHVs (61.9%) and ANM (66.3%). A significant difference was observed between SNs and ANM with regard to intranatal care (p=0.011) and management of complications (p<0.001). Conclusion: Knowledge of SBA was highest in postnatal care followed by antenatal and intranatal care and lowest in management of complications. Among the different categories of SBA, knowledge with regard to intranatal care and management of complications was better in SNs than ANMs.